The Effect of Intake Temperature on the Idle Combustion Cycle Variation of Two-Stroke Aviation Kerosene Piston Engines - Jian Wang; Zhiqiang Han; Yusheng Liang; Zinong Zuo; Zhongxin Fang; Wei Tian; Jia Fang; Xueshun Wu (Energies)
In order to solve the problem of combustion cycle variation in two-stroke aviation kerosene piston engines under idle conditions, experiments were conducted to investigate the influence of intake air temperature on combustion cycle variation and output work. The coefficient of variation of the indicated mean effective pressure was used to characterize combustion cycle variation. The results showed that there is a negative correlation between the engine combustion work and the combustion cycle variation. In the lower range, increasing the intake air temperature has a greater effect on reducing the combustion cycle variation, while in the higher range, the combustion cycle variation has a greater impact on the output work. At the same time, the influence of intake air temperature on the fuel evaporation rate is related to engine speed, and this relationship weakens as the engine speed increases. In the range of 0~40 °C, the higher the intake air temperature, the larger the stable combustion range.